Pengaruh Keterampilan Mengajar, Self Efficacy, dan Motivasi Intrinsik Terhadap Kesiapan Menjadi Guru: The Influence of Teaching Skills, Self-Efficacy, and Intrinsic Motivation on Teacher Readiness - Nuraisyah, Siska; Sartika, Sri Hardianti; Aisyah, Iis (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to determine the influence of teaching skills, self-efficacy, and intrinsic motivation on the teacher readiness of students from the 2021 cohort at the Faculty of Teacher Training and Education, Siliwangi University. Teacher readiness is a critical factor in education, determined by pedagogical abilities, self-belief, and an individual's internal drive to contribute to the teaching and learning process. This research employed a quantitative approach with a survey method, using a questionnaire as the instrument distributed to respondents. The research sample was selected using a simple random sampling technique. Data analysis was conducted using multiple linear regression to test the influence of each independent variable on the dependent variable. The t-test results indicated that each independent variable has a significant influence on teacher readiness. The F-test demonstrated that all three variables simultaneously have a significant effect on student teacher readiness. Furthermore, the coefficient of determination (R Square) test yielded a value of 0.693, signifying that 69.3% of the variation in teacher readiness can be explained by teaching skills, self-efficacy, and intrinsic motivation. The remaining 30.7% is influenced by other factors not examined in this study. Therefore, these three variables are crucial factors that can enhance students' readiness to become teachers.